Kajian Hilangnya Nilai Budaya (Cultural Losses) dalam Terjemahan Bahasa Inggris Cerpen Karya Pramoedya Ananta Toer - en_US, Novalinda; Zulprianto; en_US, en_US (Kementerian Sekretariat Negara Republik Indonesia, 2017)
Abstract This article describes the types of cultural losses found in the English versions of two short stories by Pramoedya Ananta Toer entitled Inem and Yang Sudah Hilang which were translated into English as Inem and All That Is Gone by Willem Samuels. It is widely accepted that languages may have have shared or particular cultural properties. While universal properties of source language (SL) can be easily transferred into target language (TL), particular properties of SL into TL may be translated with certain challenges. This is due to the fact that an SL lexicon, denoting an object or a concept, may not readily have an equivalent in the TL. This is in fact the frequent problem encountered in translating texts containing cultural words, including literary works, and so translators are conditioned to negotiate their meaning in order that loss can be mitigated. The result of analysis shows that there are three types of cultural losses found in the translation of the two short stories, they are, implicit loss, modified loss, and complete loss. Keywords : Short story, cultural word, cultural losses